Determining Optimum EDM Parameters in Drilling a Small Hole by Taguchi Method - A. R., Yusoff; Z., Ghazalli; Hazami, Che Hussain (Interscience, 2009)
Electro Discharge Machining (EDM) process uses electric sparks to generate high temperature and melts the workpiece material. In drilling process of EDM, electro thermal mechanism between electrode and workpiece creates a hole. The present study performs Taguchi method to search the optimal process parameters for high speed super drill machine that was used to make a small hole from aluminium material. An Orthogonal (OA) array, main effect, Signal-to-Noise (S/N) ration and Analysis of Variance (ANOVA) were employed to investigate the hole size of the copper electrode of diameter 1.0 mm penetration. The optimum EDM hole process can be established through this method and the major parameters that effect the hole enlarge can be also detected and verified the effectiveness through experimental results.